Arystotelesowska tradycja rozwoju filozofii nauki i edukacji w kulturze europejskiej = Arystoteles's tradition development of philosophy of sciences and education in European culture - Gnitecki, Janusz (1945-2008) (Zielona Góra: Uniwersytet Zielonogórski)
Pitagoras-Platon's, Arystoteles's, Archimedes-Euklides's and hermeneutic tradition of development of philosophy of sciences and education is presented in European culture. The subject of interest in this article is Arystoteles's tradition in European culture. This tradition is shown in five stages: (l) ancient, (2) premodernity, (3) modernity, (4) postmodernity and (5) modernity and postmodernity.
Keywords: filozofia nauki; edukacja; Arystoteles (filozof; 384 p.n.e.-322 p.n.e.)